Business ethics : [rights, justice, morals, values] - Gavai, A. K. (Himalaya Pub. House, 2016)
This book includes these contents: *Business Ethics-A Conceptual Framework, *Philosophical Foundation of Ethics-I, *Philosophical Foundation of Ethics-II, *Moral Duty, Rights and Justice, *Business and Society, *Values and Society, *Ethics at Work-Place-I, *Ethics at Work-Place-II, *Institutionalising the Ethics.